Associated evolution of fruit size, fruit colour and spines in Neotropical palms. (15th April 2020) - Nascimento, Lucas Ferreira do; Guimarães, Paulo R.; Onstein, Renske E.; Kissling, W. Daniel; Pires, Mathias M.
Abstract: Understanding how ecological interactions have shaped the evolutionary dynamics of species traits remains a challenge in evolutionary ecology. Combining trait evolution models and phylogenies, we analysed the evolution of characters associated with seed dispersal (fruit size and colour) and herbivory (spines) in Neotropical palms to infer the role of these opposing animal–plant interactions in driving evolutionary patterns. We found that the evolution of fruit colour and fruit size was associated in Neotropical palms, supporting the adaptive interpretation of seed‐dispersal syndromes and highlighting the role of frugivores in shaping plant evolution. Furthermore, we revealed a positive association between fruit size and the presence of spines on palm leaves, bracteas and stems. We hypothesize that interactions between palms and large‐bodied frugivores/herbivores may explain the evolutionary relationship between fruit size and spines. Large‐bodied frugivores, such as extinct megafauna, besides consuming the fruits and dispersing large seeds, may also have consumed the leaves or damaged the plants, thus simultaneously favouring the evolution of large fruits and defensive structures. Our findings show how current trait patterns can be understood as the result of the interplay between antagonistic and mutualistic interactions that have happened throughout the evolutionary history of a clade. Abstract : We investigated how plant‐animal interactions can shape plant traits. By exploring the relationship between fruit size, fruit color and spines, our analyses suggest that the interplay between mutualisms (seed dispersal) and antagonism (herbivory) affected the macroevolutionary dynamics of Neotropical palms generating an association between fruit color, fruit size and plant spinescence.